ELABORATING COMMUNICATIVE COMPETENCE IN JUNIOR CLASSES - Ribinskaya Elvira Grigoryevna (Western European Studies, 2023)
Communication is of the most important categories of human life being both the expression and condition of social life. With the increasing participation of any individual in the society, the interactive efficiency is formed and developed. It allows a man to exist in a social group, understand the relationships among the participants of social life and successfully accomplish their own objectives. The issues of language communication as one of the most important categories of human functioning, which is both an expression and condition of social life, are discussed in the article. The issues concerning acquisition and development of language fluency in terms of communication and culture, with special emphasis placed on the effect of family relationships on their formation are also discussed.
Keywords: Language communication; language fluency; communicative competence